The STUDI PUSTAKA PENERAPAN ACTIVITY BASED COSTING PENENTUAN TARIF LAYANAN DI RUMAH SAKIT - Diah Anugrah Sharasanti (Universitas Katolik Darma Cendika, 2023)
This study aims to provide literacy regarding the implementation of Activity Based Costing in determining cost product in hospitals in Indonesia. Several studies have found that many hospitals calculate the rates for their services using unit costs based on the calculation of the cost of production which does not reflect actual activity, resulting in errors in decision making on service rates. According to Supriono (1999) in Andriyansah et all (2013), Hospitals in determining the cost of products, sometimes still use traditional cost accounting, where this system is not suitable for advanced manufacturing environments, and with high product diversification. This research is a literature study on the implementation of Activity Based Costing in Indonesian hospitals. The data collection method is a literature study of 14 (fourteen) studies on the ABC system used by hospitals for the period 2012 to 2023. The results of the study show that Activity Based Costing is an effective tool in service companies to be able to trace costs of services provided. generated and assists in the implementation of total quality in service companies by encouraging management to analyze activities and determine their value to customers. However, several studies have shown that not all service companies, especially hospitals, can implement this system. Sarokolaei (2012) found that the banking sector in Iran that there is no significant difference between fees calculated by setting Activity Based Costing and by traditional methods for current bank deposits and deposits, so that the application of Activity based costing in service companies depends on how the company understands Activity Based Costing and determining variable costs.